Providing a Model for Digital Transformation of Customer Experience in Acquiring Insurance Services (Case Study: Asia Insurance) - Nikougoftar, Mostafa; Heydariyeh, Seyed Abdollah; Faezi Razi, Farshad (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective:  This study aims to develop a model for the digital transformation of customer experience in acquiring insurance services, focusing on identifying the causal, intervening, contextual, strategic, central phenomenon, and outcome factors involved in this transformation.Methods and Materials: The research employs a mixed-methods approach, utilizing both qualitative and quantitative data. The qualitative data were collected through interviews with 10 experts in the insurance industry, and analyzed using manual coding based on the grounded theory method with Strauss and Corbin’s systematic approach. The quantitative data were obtained using a questionnaire distributed to insurance customers, and analyzed using Smart PLS software. The study evaluates the structural model fit using R², Q², and SRMR indicators to ensure the validity and reliability of the proposed model.Findings: The analysis identified six main factors influencing the digital transformation of customer experience: causal conditions (technological advancements, changing customer expectations, increased competition, economic benefits), central phenomenon (digital transformation of the insurance industry, focus on customer experience, agility and flexibility, focus on customer expectations), intervening conditions (cultural and organizational barriers, data-related challenges, regulatory complexities, cybersecurity concerns), contextual conditions (automation, personalization, e-commerce, multiple experiences, innovations), strategies (customer focus, appropriate technology use, creating a digital culture, forming strategic partnerships, measuring and analyzing results), and outcomes (improved customer satisfaction and loyalty, cost reduction, increased conversion rates, access to new markets, innovation, increased speed and ease of operations, cybersecurity concerns, digital divide, overreliance on technology, job loss, privacy issues).Conclusion: The study presents a comprehensive model for the digital transformation of customer experience in the insurance industry, validated through qualitative and quantitative analysis. The model highlights the importance of leveraging technological advancements and addressing organizational and regulatory challenges to enhance customer experience.